The Relationship Between The Level Of Knowledge On The Use Of Over-The-Counter And Limited Over-The-Counter Drugs And Self- Medication Behavior In The Community Of Perkebunan Sei Parit Village - Isna Wardaniati; Ikha Hafni Putri; Vonny Kurnia Utama (Jurnal Ilmu Kesehatan Abdurrab, 2025)
This study investigates the relationship between knowledge levels and selfmedication behavior concerning over-the-counter (OTC) and limited OTC drugs in Perkebunan Sei Parit Village. Employing a quantitative cross-sectional design with 208 respondents (aged 17-40) via purposive sampling, data were collected through questionnaires and analyzed using the Chi-Square test (SPSS 27). Results indicate that the majority of respondents (65,4%) possess good knowledge of selfmedication. Self-medication behavior was categorized as good (45,7%), though significant proportions were sufficient (34,6%) and poor (19,7%). A significant relationship was found between knowledge level and self-medication behavior (pvalue = 0,000), confirming that better knowledge promotes more appropriate practices. Popular self-medication drugs include Paracetamol, Komix, Entrostop, and Promag. Healthcare professionals (76,0%) serve as the primary information source, and pharmacies (78,8%) are the main drug acquisition point. This study recommends enhanced health education to foster safe and rational self-medication